Massive Ileal Bleeding Secondary to a Dieulafoyʼs lesion - Becq, Aymeric (Endosc Int Open, 2018)
Dieulafoyʼs lesions are a rare cause of gastrointestinal bleeding. This article presents the case of a young woman presenting with a massive ileal bleeding, secondary to a Dieulafoyʼs lesion. A computed-tomography angiography scan showed an arterial bleeding in the ileum and the diagnosis was confirmed by an emergency peroperative enteroscopy. Surgical treatment was performed. Dieulafoyʼs lesions account for 1 % to 2 % of acute gastrointestinal bleeding and lesions are mostly located in the upper gastrointestinal tract. This case stresses that Dieulafoyʼs lesions can be located in the lower gastrointestinal tract and that in such cases, diagnostic imaging and surgical treatment are often warranted.